Effects of layered clothing on the post-mortem decomposition of rat carcasses on grass bushes and dead leaves - Noor Hazfalinda Hamzah; Darishini Manimaran; Khairul Osman; Nur Mahiza Md Isa; Gina Francesca Gabriel (Penerbit Universiti Kebangsaan Malaysia, 2022)
A post-mortem decomposition is defined by the evaluation of the physical and chemical changes of a cadaver or a carcass in order to estimate the cause of death and the time of death. The purpose of this study is not to replicate a real crime scene but to enhance knowledge of the effects of clothing in a decomposition process, mainly, the effects of layered cotton clothing on the post-mortem decomposition of adult female rat carcasses. Fifteen rats were divided into three groups: control, one-layered and two-layered clothed. The control subjects were unclothed and used to compare the post-mortem changes with the clothed subjects, one-layered and two-layered rat carcasses. All subjects were placed outdoor, 2.5 meters away from each other on grass bushes and dead leaves. Ambient temperature and humidity were recorded to observe if it associates with the post-mortem changes of the rats. Insect activity on each subject was observed. Post-mortem changes were measured using the Total Body Score system. The results showed that the control group underwent a faster decomposition compared to the clothed groups. The different layers of clothing did not show a vast difference in post-mortem changes. The ambient temperature of 28°C influences the post-mortem decomposition. The decomposition was rapid under the dominance of maggots compared to ants as ant colonies delayed the decomposition process. The study gave the knowledge of the effect of clothing in decomposition of female rats in forensic science.